Rising Customer Loyalty with Beneficial Impact on Service Quality Dimensions during the COVID-19 Pandemic for Tourism in Thailand - MUSRIHA, Musriha; RAPITASARI, Diana (Journal of Environmental Management and Tourism, 2023)
The tourism industry is one of the fastest and largest growing industries in the economy nowadays. This industry has proven to be full of opportunities and challenges such as opening international borders, widespread internet access, and increased mobility and wealth of citizens in increasingly industrialized countries such as Thailand. The tourism industry can support the economic development of both local and country economic, earnings from foreign and domestic visitors. Especially during the COVID-19 pandemic, the tourism industry is declining. Therefore, some adjustment is required to increase the recovery rate of the tourism industry.  The goal of this study is to assess the influence of service quality (SERVQUAL) dimensions on customer loyalty using customer satisfaction as an intervening variable. Based on SERVQUAL dimension as the independent variable and customer loyalty as the dependent variable also customer satisfaction is the intervening variable. This research was done in 4 stars hotels in Thailand, that struggle during the COVID-19 pandemic. The data used is based on the questionnaire that spread out to 100 respondents of hotel customers from many countries.  The regression and analysis approaches are used in this research because the goal is to determine the indirect influence of SERVQUAL characteristics and customer satisfaction on customer loyalty. The result of the study showed a positive impact to increase the value of the customer and minimizing customer loss, especially during the COVID-19 Pandemic.